Twitter'daki Dini ve Etnik Temelli Nefret Söylemlerinin Analizi - (:unkn) unknown (My University, 2016)
Alan literatürüne göre sosyal medya ve sanal evren, toplumsal yaşamda çatışma ve anlaşmazlıklara kolaylaştırmaktadır. Başta etnik ve inanç temelli söylemler olmak üzere her türlü nefret söylemi, başta azınlıkları ve dezavantajlı grupları hedef almakta; toplumsal huzuru, birlikte yaşama kültürünü ve vatandaşların kişilik haklarını tehdit etmektedir. Bir sosyal medya platformu olan Twitter, söylemlerin daha kolay üretilmesi, daha hızlı yaygınlaşması ve etkisini katlayarak artırması yönüyle basılı ve geleneksel medyadan anlamlı biçimde farklılaşmaktadır. Twitter'ın kullanıcıya sunduğu ara yüz özelliklerinin analizi ve kullanıcıların burada üretip dolaşıma soktukları dini ve etnik temelli nefret içerikli paylaşımların söylem analizi, literatürdeki iddiaları Türkiye açısından doğrulamaktadır. Araştırmanın sonunda; gittikçe karmaşıklaşan, çok kültürlü ve çok kimlikli hâle gelen toplumlarda birlikte yaşama kültürünü tehdit eden nefret söylemini azaltma potansiyeli olan uygulamalara yer verilmiştir.

In this reaserch, the production and circulation of hate speech on the Twitter is analyzed by using method of discourse analysis of van Dijk. The properties of social network sites and freedom given by them illusions that provide the users can be misused and this can cause hatred, prejudice and discriminatory contents that addresses to differences of the society. Hate speeches in social media have a quite different ways than main-stream media because of its constructional nature. Twitter can be quickly spreading for functions of environment such as follow and retweet. Countries like Turkey -where many ethnic and religious groups live and democracy is not strong enough- discrimination, prejudice and hate speech against differences can be occurring frequently. Hate speech can produce and enter into circulation much easier according to features of media so it is perceived as a normal. The purpose of this study is to analyze factors that facilitate the formation of hate speech in social media and to investigate the ethnic and faith-based hate speech produced by the impact of these elements. In addition to this, end of the reaserch, a number of proposal to fight against hate speech are presented in Turkey.
Analysis of Religious and Ethnic Hate Speech on Twitter